Applications of A Shehu Transform to the Heat and Transport Equations - Neamah ALbukhuttar, Athraa; Dheyaa Ridha, Zainab; Neamah Kadhim, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The Shehu transform principle properties were shown by Maitama [13]. Atheros in 2019 used the Shehu transform to solve differential equations. In this paper, we introduce the Shehu transform, which is used in the solution of ordinary and partial differential equations. Moreover, we extended the Shehu transform application for solving transport and heat equations that satisfied known or unknown initial conditions.